The contributions of Marshall McLuhan to the field of Educommunication:: dialogues with Freirean thought (Intercom - Brazilian Journal of Communication Sciences, 2026)
According to Kuskis and Logan (2013), one of Marshall McLuhan’s mainconcerns was education, although he is not widely recognized for his studiesin this field. Despite having published only two books specifically on thesubject, his ideas can be accessed through lectures, interviews, and othermedia appearances. Based on detailed research conducted in libraries inCanada, McLuhan’s home country, this paper aims to identify possibleconnections between the ideas of Freire and McLuhan, as well as to explorethe aspects that distinguish them. By applying the Laws of Media (McLuhan,M.; McLuhan, E., 1988) to Freirean and McLuhanian thought, consideringthe classroom as a medium, it is concluded that McLuhan can be seen as aneducommunicator and that his studies offer significant contributions to thefield of Educommunication.
Keywords: Education; Communication; Educommunication; Media Ecology; media.